Continuous Professional Development Centered on Learning Needs - Riganti, Paula; Alurralde, Micaela B.; Ganiele, María N.; Sigal, Tamara V.; Gavoto, Leticia; Terceiro, Diego R.; Arceo, Dolores (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: for some time now, our institution has offered continuing medical education activities to its physicians, but these were never formally evaluated. We set out to assess the current academic program and redesign the educational proposal based on the participants' learning needs (LN).Development: in 2021, we assessed satisfaction with the current academic program and explored LN using three gathering methods: a survey, focus groups, and a questionnaire. With this data, we designed a new continuing professional development (CPD) proposal that we implemented in 2022 and evaluated at the end of 2022 using a new survey.Results: in 2021, 90 out of 148 physicians (61%) completed a survey; 16 responded to the questionnaire, and 73 participated in focus groups. Participants mentioned several areas where they would like to receive training and the fundamental skills that make up the family physician's practice. Some activities in the current program were valued and responded well to the LNs, but others received criticism for lack of usefulness and relevance to practice. With this information, for 2022, we designed a new educational proposal suggesting 12 thematic axes with didactic, practice-oriented activities, where each participant chose what to train in. At the end of 2022, 58 out of 148 physicians (39%) responded to the evaluation survey. Most of them found the activities helpful and were motivated to participate by interest in the subject and time availability. There was good participation in the activities, although the workload of the teaching teams also increased as the number of activities increased.Conclusion: the new proposal provided greater flexibility, accessibility, and autonomy in continuing education and was well-rated. The next challenge is to continue to evaluate how we can maintain the satisfaction and quality of the program without overloading the teaching teams.
Keywords: continuous professional development; curriculum design; evaluation